2009
DOI: 10.1258/jrsm.2009.090092
|View full text |Cite
|
Sign up to set email alerts
|

Independent sector treatment centres: the first independent evaluation, a Scottish case study

Abstract: SummaryObjectives The £5 billion English Independent Sector Treatment Centre (ISTC) programme remains unevaluated because of a lack of published contract data and poor quality data returns. Scotland has a three-year pilot ISTC, the Scottish RegionalTreatment Centre (SRTC), the contract for which is now in the public domain.This study aims to conduct an independent evaluation of the performance of the SRTC during the first year of operation.Design A retrospective analysis of the SRTC comparing activity as repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…The total cost of these two commissioning phases was estimated at £2.7bn. 2 The first wave of private treatment centres were paid 11% above the price for equivalent treatment in the NHS, even though they had lower staffing costs, offered inferior pensions and claimed that their 'private sector' mentality made them more efficient. 3 Moreover, they were paid irrespective of whether contracted volumes were delivered.…”
Section: Introductionmentioning
confidence: 99%
“…The total cost of these two commissioning phases was estimated at £2.7bn. 2 The first wave of private treatment centres were paid 11% above the price for equivalent treatment in the NHS, even though they had lower staffing costs, offered inferior pensions and claimed that their 'private sector' mentality made them more efficient. 3 Moreover, they were paid irrespective of whether contracted volumes were delivered.…”
Section: Introductionmentioning
confidence: 99%
“…1 The financial implications of this agreement have been demonstrated in a study which reported on the results from the first year of operation of an ISTC in Scotland. 6 The authors commented that the annual contract was based on the number of referrals made to the ISTC and not from the treatments carried out. The requisite number of referrals was managed during the time period but only 32% of these patients underwent a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the shortcomings of ISTCs have been well documented. [6][7][8] Bannister et al compared the outcomes for total replacement of the hip and knee carried out in a local AHT compared with two regional ISTCs. 8 They reported considerable variation in outcome, with a marked increase in the prevalence of reoperation and wound complications, as well as a trend towards a higher prevalence of hospital readmission for arthroplasty, carried out at ISTCs.…”
Section: Discussionmentioning
confidence: 99%
“…ISTC contracts were designated “commercially confidential,” thereby keeping them outside the Freedom of Information Act. One study of a Scottish ISTC indicated that large payments were being made for patients who were not actually treated 29. ISTCs have also been shown to engage in “up-coding,” where patients are categorised as having more severe conditions than they actually have, in order to charge higher payments 30…”
Section: Size Power and Influencementioning
confidence: 99%